Phytoestrogens, bisphenol A and steroid hormones in selected human samples from Malaysia / Rafidah Hod - Rafidah, Hod (2017)
There are many endocrine disrupting chemicals (EDCs) that humans are exposed to, whether accidental or upon occupational exposure. EDCs disrupt the normal endocrine function and may cause endocrine related cancers such as prostate and breast cancer. Research has proven there are interaction effects between EDCs which can either be additive, synergistic or antagonistic. Therefore, with many possible EDCs present in one individual, the net effect could vary. A smaller group of EDCs known as oestrogenic EDCs can originate from natural sources or it can be synthetic in nature. These EDCs mainly produce effects related to the actions of oestrogen. Though EDC levels detected may not reach toxicity level, its presence at low level and the occurrence of combination of EDCs may still cause unwarranted effects over time, or cause further damage due to its cumulative presence in the body. This research is important in exploring the extent of oestrogenic EDC exposure and its effects on selected sex hormones in various adult populations. The choice of oestrogenic EDCs to be analysed is based on the oestrogenic EDCs which these populations are more commonly exposed to. They are soy isoflavones, a natural source of EDC and bisphenol A which is man-made and their common exposure route is via oral intake. Method development and analysis of isoflavones (daidzein, genistein, equol, formononetin, biochanin A), bisphenol A, and sex hormones (oestrone, oestradiol, testosterone) was conducted using liquid chromatography tandem mass spectrometry (LCMSMS) for blood and breast tissue matrices. Biological samples were collected iv from two separate populations. The first population involved 225 male volunteers who practiced vegetarian or non-vegetarian diet while the second population was among 252 female patients in a university hospital who were treated for breast pathology and non-breast pathologies. It was found that among the male population, vegans had the highest percentage of equol producers. Chinese males who are non-vegetarians and consumed daidzein and biochanin A tend to have higher testosterone level than other groups. Male equol producers tend to be protected from an increased tendency of a high testosterone level even with consumptions of various isoflavones compared to non-equol producers. Non-equol producers however could have a lower testosterone level upon consumption of equol-rich foods. Among the female subjects, equol producers tend to have a lower oestradiol levels with higher consumption of all isoflavones. This supports the idea of equol playing a role in preventing adverse effects of EDCs. Higher concentration of isoflavones was present in the plasma than in the breast tissue. Highest concentration of EDC found in breast tissue was BPA which was 115 times higher than in plasma. There was no meaningful association of EDC concentrations and hormone levels in the breast tissue except for oestrone which correlated positively with BPA in Malay subjects and with formononetin in menopausal subjects. Despite the lack of correlation with oestradiol, the extent of BPA bioaccumulation in the breast tissue which may have occurred over time and through countless unintentional exposure is still a major concern.